Determinant Analysis on the Efficiency of Small-scaled Corn Agribusiness: Empirical Evidence from Central Java, Indonesia - Sri Rahayu (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
This research aims to identify the efficiency of corn agribusiness in Central Java Indonesia and the factors affecting it. The research method used was DEA (Data Envelopment Analysis) with output-oriented assumption to measure each of the LKMA being observed. Afterwards, the researchers used Ordinary Least Squares (OLS) regression analysis to analyze the factors affecting the level of efficiency of the corn agribusiness. The findings show that majority of corn agribusiness is inefficient. Based on the DEA-CRS calculation, 11 (18.33%) corn agribusinesss are efficient, while based on the DEA VRS calculation, 18 (30%) corn agribusinesss are efficient. Arable land size, corn agribusiness’ experience, and land ownership status are affecting the level of efficiency.